The Effect of Gobak Sodor Based Outdoor Learning on Seventh Grade Students Collaborative Character In Algebra - Ajeng Prasasti Pasaribu; Sofnidar; Dewi Iriani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2026)
The development of collaborative character is one of the important demands in 21st-century education. However, mathematics learning in schools still tends to be teacher-centered and emphasizes cognitive aspects, resulting in limited opportunities for students to develop collaborative skills. Initial observations at SMP Negeri 7 Muaro Jambi indicate that students’ collaborative character in mathematics learning is relatively low, and outdoor learning based on traditional games has not been optimally implemented. In addition, studies that integrate traditional game-based outdoor learning into mathematics learning with a primary focus on students’ collaborative character remain limited. This study aims to analyze the influence of outdoor learning based on the traditional Gobak Sodor game on students’ collaborative character in mathematics learning. This study employed a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of grade VII students divided into an experimental class and a control class. Data were collected using validated collaborative character questionnaires and observation sheets. Data analysis was conducted using descriptive statistics and inferential analysis with the Mann–Whitney U test. The results showed that the average posttest score of students’ collaborative character in the experimental class reached 13.84 67.41, which was higher than the control class with an average score of 20.74 57.28. The hypothesis testing results indicated a significant difference between the two groups with an Asymp. Sig. (2-tailed) value of 0.005 < 0.05. These findings indicate that outdoor learning based on the traditional Gobak Sodor game has a positive effect on improving students’ collaborative character in mathematics learning. This learning approach can serve as an innovative alternative for mathematics teachers and contributes theoretically to mathematics education oriented toward character development.